Harmonization of diagnostic criteria in mastocytosis for use in clinical practice: WHO vs ICC vs AIM/ECNM: special article - Valent, Peter; Hartmann, Karin; Hoermann, Gregor; Reiter, Andreas; Alvarez-Twose, Iván; Brockow, Knut; Bonadonna, Patrizia; Hermine, Olivier; Niedoszytko, Marek; Carter, Melody C.; Butterfield, Joseph H.; Siebenhaar, Frank; et al. (The journal of allergy and clinical immunology. In practice, 2024)
Mastocytosis is a clonal myeloid disorder defined by an increase and accumulation of mast cells (MCs) in one or multiple organ systems. The complex pathology of mastocytosis results in variable clinical presentations, courses, and outcomes. The World Health Organization (WHO) divides the disease into cutaneous mastocytosis (CM), several forms of systemic mastocytosis (SM), and MC sarcoma. In most patients with SM, a somatic KIT mutation, usually D816V, is identified. Patients diagnosed with CM or nonadvanced SM, including indolent SM, have a near-normal life expectancy, whereas those with advanced SM, including aggressive SM and MC leukemia, have limited life expectancy. Since 2001, a multidisciplinary consensus group consisting of experts from the European Competence Network on Mastocytosis and the American Initiative in Mast Cell Diseases has supported the field by developing diagnostic criteria for mastocytosis. These criteria served as the basis for the WHO classification of mastocytosis over 2 decades. More recently, an International Consensus Classification group proposed slightly modified diagnostic criteria and a slightly revised classification. In this article, these changes are discussed. Furthermore, we propose harmonization among the proposals of the American Initiative in Mast Cell Diseases/European Competence Network on Mastocytosis consensus group, WHO, and the International Consensus Classification Group. Such harmonization will facilitate comparisons of retrospective study results and the conduct of prospective trials.